PERAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN USAHA PARIWISATA DI KAMPUNG BURICAK BURINONG - Nurhidayat, Wildan; Napu, Della Maghfira; Fakhrurrazi, Alfat; Novriando, Samuel; Wigiaharty, Alyza Ratih (Jurnal Manajemen, 2023)
This study aims to analyze the relationship between the quality of human resources (HR) and the level of tourist visits in Buricak Burinong Village, the method used in this research is quantitative. The sample studied was 100 respondents who had visited Buricak Burinong Village, data were collected through the survey method by distributing questionnaires (google form) with the Conveniance Sampling technique. Data were analyzed using multiple linear regression techniques. The results of this study indicate that simultaneously the quality of human resources has a significant influence on the level of tourist visits in Buricak Burinong Village. The results of the analysis show that there is a positive relationship between the quality of human resources and the level of tourist visits. In optimizing the level of tourist visits to Kampung Buricak Burinong, special attention needs to be paid to the intellectual quality and educational level of human resources. By improving the quality of human resources in this village it can attract more tourists and strengthen its position as an attractive tourist destination.